Analisis Risiko pada Produk Pembiayaan Arrum BPKB di Pegadaian Syariah UPS Watang Sawitto - Rachmadana; Desy Arum Sunarta; Rasyidah Bulqis (Mappideceng:Jurnal Ekonomi Syariah, 2025)
The development of Micro, Small and Medium Enterprises is often hampered by limited access to capital due to lack of eligible collateral. Arrum BPKB financing products from Pegadaian Syariah are an alternative solution, but still have potential risks. This study aims to determine the form of Arrum BPKB financing and analyze its risks at Pegadaian Syariah UPS Watang Sawitto. Using descriptive qualitative methods with data collection techniques through observation, interviews, and documentation of employees and customers. The results of this study are as follows. 1) The forms of Arrum BPKB financing at Pegadaian Syariah UPS Watang Sawitto are: a) Financing in the form of loans, where customers apply for financing with vehicle ownership certificates (BPKB) as collateral. b) The term agreed upon by the customer, according to the customer's needs. c) Storage service fees are charged. d) Financing repayment is made using a monthly installment system. 2) Risk analysis for Arrum BPKB financing products at Pegadaian Syariah UPS Watang Sawitto is carried out using risk management by: a) Identifying risks. b) Measuring risks. c) Monitoring risks. d) Controlling risks